Lived Experiences of Quarantined Muslim Students in China and Italy - Ahmad, Akhlaq (Journal of Muslim minority affairs, 2023)
The COVID-19 pandemic has been spreading in China and other parts of the world since December 2019, bringing not only the risk of infection but also immense psychological pressure. This study narrates the quarantined experiences of Muslim students studying in China and Italy during the Coronavirus pandemic. Using the phenomenological hermeneutical method, we analyzed the lived experiences of these students, encompassing psychological challenges such as uncertainty, fear, sleeplessness, helplessness, loneliness, and behavioral changes as well as body experiences. These included vulnerability, deviance, body vigilance, and thoughts of death. Coping strategies involved religion and religious practices, family, friends, volunteering, and technology including social media. This study reveals that quarantine experiences have ingrained wide-ranging and penetrating impacts on mental and physical health resulting in diverse coping strategies among those living in quarantine.